THE EFFECT OF DIFFERENT KIND OF LIQUID SMOKE MATERIALS ON THE QUALITY OF SMOKE FLAVORED CATFISH (Cryptopterus bichircis) - Hindam Sabbah; Tjipto Leksono; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study aimed to observe the effect of different kind of raw materials of liquid smoke on the quality of smoke flavored catfish (Cryptopterus bichircis). The experimental was designed as completely randomized design (CRD). The treatment was soaking catfish into different kind of solution of liquid smoke, namely liquid smoke pyrolyzed from rice husk (A1), oil palm midrib (A2), and coconut shell (A3). The catfish were soaked into the liquid smoke at a concentration of 6% for 60 minutes. Parameters to evaluate the quality of smoke flavored catfish produced were the sensory value of appearance; smell; texture; and taste, proximate composition, the content of total phenol, total acid, and pH values. The results showed that the different kind of smoke source was indicating significant effect on aroma, but not on appearance, flavor, and texture of the smoke flavored catfish. The chemical characteristics were significantly affected on the pH value and the content of total phenols, but not significantly affected on water content and the content of total acid. Based on the results of the study concluded that the best treatment was the using of the raw material of liquid smoke coconut shell (A3) which have the characteristics of smoked fish with 7.00, flavor at 7.61, texture at 6.71, and aroma at 7.29 and containing a total phenol of 5.28 ppm and pH. 4.63.Keywords: catfish smoked flavor, coconut shell, palm fronds and rice husks.